2008
DOI: 10.1353/rhe.0.0030
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Effects of Campus Racial Climate on Degree Completion: A Structural Equation Model

Abstract: Racial minority student persistence is of paramount importance to higher education policymakers and practitioners. This study was aimed at understanding racial differences in the direct and indirect effects of campus racial climate on degree completion using structural equation modeling techniques and a nationally representative sample. The findings of this analysis highlight the importance of examining conditional effects and indicate that students from disparate racial backgrounds may experience and react to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(41 citation statements)
references
References 39 publications
3
37
1
Order By: Relevance
“…While some appear to be doing well with regard to producing an equitable number of Latinx degree holders, they are operating from a, "Latinx-neutral" perspective, meaning they are not centering the experiences of Latinx students or being intentional in their efforts to create a culture that enhances the experience of Latinx students. Although there is no guarantee that creating a culture that values and embraces Latinidad will ultimately increase graduation and completion rates, research has shown that students' perceptions of the campus climate affect their persistence (Museus, Nichols, & Lambert, 2008;Rhee, 2008). Even further, Garcia (2016) suggests that HSIs should enhance college students' racial/ethnic identity and development, regardless of its effects on persistence and graduation.…”
Section: Discussionmentioning
confidence: 99%
“…While some appear to be doing well with regard to producing an equitable number of Latinx degree holders, they are operating from a, "Latinx-neutral" perspective, meaning they are not centering the experiences of Latinx students or being intentional in their efforts to create a culture that enhances the experience of Latinx students. Although there is no guarantee that creating a culture that values and embraces Latinidad will ultimately increase graduation and completion rates, research has shown that students' perceptions of the campus climate affect their persistence (Museus, Nichols, & Lambert, 2008;Rhee, 2008). Even further, Garcia (2016) suggests that HSIs should enhance college students' racial/ethnic identity and development, regardless of its effects on persistence and graduation.…”
Section: Discussionmentioning
confidence: 99%
“…Torres, 2006). Furthermore, findings showed that Latina/o students' expectations and commitments were positively related to the odds that students would successfully earn a college degree (Arbona & Nora, 2007;Cerna et al, 2009;Museus et al, 2008). Furthermore, findings showed that Latina/o students' expectations and commitments were positively related to the odds that students would successfully earn a college degree (Arbona & Nora, 2007;Cerna et al, 2009;Museus et al, 2008).…”
Section: Internal Motivation and Commitmentmentioning
confidence: 96%
“…It was anticipated that differences would emerge by site such that students in the high REM student context (Site 1) would report increased cultural fit, higher perception of mentoring, and more college and life satisfaction (Cress, 2008;Hurtado & Carter, 1997;Hurtado & Ponjuan, 2005;Museus et al, 2008). Results revealed only two differences such that students from Site 1 reported increased cultural congruity but lower life satisfaction than students at Site 2.…”
Section: Discussionmentioning
confidence: 99%
“…From demographics to university or college mission, the institutional climate immensely affects all students and, in particular, the racial climate moderates REM students' educational experiences (Cress, 2008;Hurtado & Carter, 1997;Hurtado & Ponjuan, 2005), retention, and degree completion (Museus, Nichols, & Lambert, 2008). For example, in a large-scale study of over 7000 undergraduates from 10 universities, students of color experienced harassment, hostility, and perceived their campus climate as "more racist and less accepting" than their White counterparts (Rankin & Reason, 2005, p. 43).…”
Section: J Castellanos Et Almentioning
confidence: 99%
See 1 more Smart Citation